FORMULATION AND EVALUATION OF DISPERSIBLE PELLETS OF LAGENARIA SICERARIA - Dudhamal, S S; Kawtikwar, P S; Nagoba, S N (Asian Journal of Pharmaceutical Research and Development, 2018)
Lagenaria siceraria (Bottle gourd) is a common name in every household. Its medicinal values were identified many years ago, and still people use this plant for many disorders. Extrusion spheronization technique was employed for preparation of the pellets, to study the effect of crosscarmellose sodium, on it. The pellets were prepared by use of combination of Avicel PH 101 and lactose that indicated good flow properties. The superdisintegrant used was crosscarmellose sodium between concentration 2 to 8%, to study the effect of it on the pellets. The superdisintegrant showed low disintegration time at low concentration, while as the concentration of it increased, it extended the disintegration time. Thus, optimum concentration needs to be designed for successful formulation. Batch D3 of 6% crosscarmellose sodium concentration showed the requisite characteristic in terms of all the evaluation parameters, with DT up to 50 to 55 seconds. Thus, use of this superdisintegrant alone, but in low concentration, can be helpful, or else combination of this with other superdisintegrants can be approached, or else new superdisintegrants can be tried. Thus, the study indicated the effect of superdisintegrant for formulation of dispersible pellets. Keywords: Extrusion-Spheronization, Crosscarmellose sodium, Lagenaria siceraria, Pellets